2006
DOI: 10.1016/j.cell.2006.10.017
|View full text |Cite
|
Sign up to set email alerts
|

The C Terminus of the L-Type Voltage-Gated Calcium Channel CaV1.2 Encodes a Transcription Factor

Abstract: Voltage-gated calcium channels play a central role in regulating the electrical and biochemical properties of neurons and muscle cells. One of the ways in which calcium channels regulate long-lasting neuronal properties is by activating signaling pathways that control gene expression, but the mechanisms that link calcium channels to the nucleus are not well understood. We report that a C-terminal fragment of Ca(V)1.2, an L-type voltage-gated calcium channel (LTC), translocates to the nucleus and regulates tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
342
5
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(375 citation statements)
references
References 44 publications
14
342
5
2
Order By: Relevance
“…Kubodera et al (29) also reported the production of similar fragment in HEK293T cells overexpressing Ca V 2.1. Interestingly, the C terminus of the L-type Ca V 1.2 Ca 2ϩ channel can also be cleaved and translocate to the nucleus, where it may act as a transcription factor (30). In our Sca6 KI mice, we could not detect such a small C-terminal fragment in cerebellar extracts.…”
Section: Discussioncontrasting
confidence: 39%
“…Kubodera et al (29) also reported the production of similar fragment in HEK293T cells overexpressing Ca V 2.1. Interestingly, the C terminus of the L-type Ca V 1.2 Ca 2ϩ channel can also be cleaved and translocate to the nucleus, where it may act as a transcription factor (30). In our Sca6 KI mice, we could not detect such a small C-terminal fragment in cerebellar extracts.…”
Section: Discussioncontrasting
confidence: 39%
“…It has been reported that an L-type voltage-gated Ca 2 þ channel is proteolytically cleaved to form a C-terminal fragment, which is translocated into the nucleus and alters the endogenous transcription of a wide variety of genes. 21 However, the molecular mechanisms that mediate this change in functionality in the TRPM2 protein between cancerous and non-cancerous tissues remain elusive. The difference in the subcellular locations of TRPM2 between cancerous and non-cancerous prostate cells may explain the switching of these two roles.…”
Section: Discussionmentioning
confidence: 99%
“…Upon dissociation from the channel, the Asn-Ca v 1.1 fragment migrates to the nucleus and functions as a transcriptional regulator. 97,143,144,145 #7. Arg-GlyT1A is the Ct fragment of the transmembrane GlyT1A glycine transporter.…”
Section: Monitoring Protein Fragments and Reacting To Their Accumulationmentioning
confidence: 99%